Preparation and characterization of polyamide 6 nanocomposites using MWCNTs based on bimetallic Co-Mo/MgO catalyst - A. R. Mohamed; A. J. Hassani; Z. A. Mohd Ishak (eXPRESS Polymer Letters)
Multiwalled carbon nanotubes (MWCNTs) based on bimetallic Co-Mo/MgO catalyst were produced in large scale by catalytic chemical vapor deposition method (CCVD) of methane. X-ray diffraction (XRD), transmission electron microscopy (TEM), thermogravimetric analysis (TGA) and Raman spectroscopy proved carbon nanotube (CNT) formation. As-produced multiwalled carbon nanotubes (PCNTs) and commercial ones (CCNTs) with the same diameter (10–20 nm) were melt blended with polyamide 6 (PA6). XRD patterns of nanocomposites showed applying 0.1% of both types of CNTs changed the crystalline structure of neat PA6 from α/γ form to thermodynamically more stable α-phase structure. Differential scanning calorimetry (DSC) showed both types of CNTs shifted crystallization temperature of about 10–15°C to higher temperature due to the nucleating effect of nanotubes. Furthermore, degree of crystallinity increased by about 30% in some composites, especially for PCNTs. Nanocomposites containing PCNTs exhibited improvements in thermal decomposition temperature in comparison with CCNT nanocomposites. Nanocomposites melt viscosity increased at high CNTs loading due to the filler-matrix entanglements.